Resting-state EEG associated with clinical measures to predict upper limb motor recovery of subacute stroke - Ding, Ling; Tian, Xiang; Ren, Huiming; Chen, Zihang; Shu, Xiaokang; Chen, Shugeng; Jia, Jie (Frontiers in Neurology, 2025)
BackgroundAfter stroke, upper limb dysfunction seriously affects patients’ quality of life. The uncertain prognosis of patients poses a challenge for therapists in developing personalized rehabilitation programs. Electroencephalograph (EEG) power spectrum changes during rehabilitation training may have a predictive effect on the improvement of upper limb movement. Therefore, it is of great clinical significance to explore the EEG power spectrum related to the recovery of upper limb function after stroke.MethodThis study included 113 subacute stroke survivors who were treated with routine rehabilitation for 2 weeks. At week 0 (T0) and week 2 (T2), behavioral scales including Fugl-Meyer Assessment of Upper Limb (FMA-UL), action research arm test (ARAT), modified Barthel index (MBI), and National Institutes of Health Stroke Scale (NIHSS) was assessed to compare correlations and observe the relationship between behavioral indicators and function under conventional rehabilitation. Twenty-six of the 113 patients were selected to undergo resting state EEG detection at week 0 (T0), week 1 (T1) and week 2 (T2), respectively. Power spectrum (PSD) and BSI values were calculated by EEG spectral analysis. The relationships between beta PSD and the clinical scales, between BSI and the clinical scales were examined by correlation and regression analysis.ResultsBehavioral scales at T0 and T2 were positively correlated in both cohorts (N = 113, N = 26). Beta PSD correlated with FMA-UL (T1: r = 0.469, p = 0.016*; T2: r = 0.391, p = 0.048*) and ARAT (T0: r = 0.412, p = 0.037*; T1: r = 0.453, p = 0.021*; T2: r = 0.487, p = 0.012*). Beta BSI negatively correlated with Brunnstrom-UL (T2: r = −0.498, p = 0.01*), FMA-UL (T1: r = −0.441, p = 0.036*; T2: r = −0.507, p = 0.008*), and MBI (T2: r = −0.457, p = 0.019*). PSD-T0 predicted FMA-Hand (β = 0.997, p = 0.014*); PSD-T1 predicted ARAT (β = 1.945, p = 0.014*). BSI-T1 predicted Brunnstrom-Hand (β = −401.7, p = 0.049*) and FMA-UL (β = −194.4, p = 0.041*), demonstrating beta EEG’s prognostic value.ConclusionResting state EEG indicators, including beta PSD and BSI, may serve as prognostic biomarkers for upper limb motor function recovery of stroke survivors, providing valuable reference for further clinical decision-making.